(untitled) (Research, Society and Development, 2021)
Objective to evaluate, through auditing, the effectiveness of nursing records in a public hospital in Goiás. Method This is a descriptive and analytical study, carried out on medical records of patients hospitalized in a public hospital in Goiás. hospital stay longer than five days in neonatal, pediatric and maternal intensive care units. For data analysis, we used the comparison of means of continuous variables through the Mann-Whitney test. Results it was verified that the inadequate filling of the medical records compromised the quality criteria, before and after the educational action. However, the means inherent to complete, incomplete and unfilled information in relation to medical records were significantly repaired after the educational action (p<0.05). The categories, identification data (PP=81.16%) and the execution of medical orders (PP=89.13%) had higher adequacy rates regarding complete records. The nursing prescription compromised the quality, regarding the incorrect filling of the records in (PP=6.76%). Conclusion nursing records do not meet the quality criteria, even after the educational action, considering that the effectiveness of the records underwent minor adjustments. It is recommended that educational actions be instituted in the hospital’s health policies.